I have three functions, $f,g,h$ that all map from $[a,b]$ to $\mathbb{R}$. I know the following:

$$f(x) \leq g(x) \leq h(x)\ \forall x\in [a,b] $$ $$x_0 \in (a,b)$$ $$f(x_0)=h(x_0)$$ $$h'(x_0) \ \& \ f'(x_0) \ exist$$

I want to show that $g'(x_0)$ exists and that $g'(x_0)=f'(x_0)=h'(x_0)$

Any suggestions? I'm really lost. I tried applying the definition of something being differentiable at a point but made no progress.


Consider the definition:

$g$ is differentiable at $x_0$ if $$ \lim_{x\to x_0}\frac{g(x_0)-g(x)}{x-x_0} $$ exists or equivalent if $$ \liminf_{x\to x_0}\frac{g(x_0)-g(x)}{x-x_0}=\limsup_{x\to x_0}\frac{g(x_0)-g(x)}{x-x_0}. $$ or equivalent if $$ \lim_{\substack{x\to x_0\\x>x_0}} \frac{g(x_0)-g(x)}{x_0-x} \text{ and } \lim_{\substack{x\to x_0\\x<x_0}} \frac{g(x_0)-g(x)}{x_0-x} $$ exist and are equal.


The limit $$ \lim_{\substack{x\to x_0\\x>x_0}} \frac{g(x_0)-g(x)}{x_0-x} $$ exists if $$ \liminf_{\substack{x\to x_0\\x>x_0}}\frac{g(x_0)-g(x)}{x-x_0}=\limsup_{\substack{x\to x_0\\x>x_0}}\frac{g(x_0)-g(x)}{x-x_0}. $$ and analogue for $<$ insteat of $>$.


Now we have $g(x_0)=f(x_0)=h(x_0)$. If $x<x_0$ we get $$ \frac{h(x_0)-h(x)}{x_0-x}= \frac{g(x_0)-h(x)}{x_0-x}\leq \frac{g(x_0)-g(x)}{x_0-x}= \frac{f(x_0)-g(x)}{x_0-x}\leq \frac{f(x_0)-f(x)}{x_0-x} $$ and for $x>x_0$ we get $$ \frac{h(x_0)-h(x)}{x_0-x}= \frac{g(x_0)-h(x)}{x_0-x}\geq \frac{g(x_0)-g(x)}{x_0-x}= \frac{f(x_0)-g(x)}{x_0-x}\geq \frac{f(x_0)-f(x)}{x_0-x} $$ Since $f$ and $h$ are differentiable at $x_0$ we get \begin{align*} f'(x_0)&=\lim_{x\to x_0}\frac{f(x_0)-f(x)}{x_0-x}= \lim_{\substack{x\to x_0\\x>x_0}}\frac{f(x_0)-f(x)}{x_0-x} \\&\leq \lim_{\substack{x\to x_0\\x>x_0}}\frac{h(x_0)-h(x)}{x_0-x} =\lim_{x\to x_0}\frac{h(x_0)-h(x)}{x_0-x}=h'(x_0) \end{align*} and \begin{align*} f'(x_0)&=\lim_{x\to x_0}\frac{f(x_0)-f(x)}{x_0-x}= \lim_{\substack{x\to x_0\\x<x_0}}\frac{f(x_0)-f(x)}{x_0-x} \\&\geq \lim_{\substack{x\to x_0\\x<x_0}}\frac{h(x_0)-h(x)}{x_0-x} =\lim_{x\to x_0}\frac{h(x_0)-h(x)}{x_0-x}=h'(x_0) \end{align*} From $f'(x_0)\leq h'(x_0)$ and $f'(x_0)\geq h'(x_0)$ we get $f'(x_0)=h'(x_0)$ and you can conclude $$ \lim_{x\to x_0} \frac{h(x_0)-h(x)}{x_0-x}=\lim_{x\to x_0} \frac{g(x_0)-g(x)}{x_0-x}=\lim_{x\to x_0} \frac{f(x_0)-f(x)}{x_0-x} $$

If you think, the last argument is to sloppy you can extend the last argument following way:

Since $ \frac{h(x_0)-h(x)}{x_0-x}\leq \frac{g(x_0)-g(x)}{x_0-x}$ for all $x\in(a,x_0)$ you get $$ \liminf_{\substack{x\to x_0\\x<x_0}}\frac{h(x_0)-h(x)}{x_0-x}\leq \liminf_{\substack{x\to x_0\\x<x_0}}\frac{g(x_0)-g(x)}{x_0-x} $$ and $\frac{g(x_0)-g(x)}{x_0-x}\leq \frac{f(x_0)-f(x)}{x_0-x}$ for all $x\in(a,x_0)$ imply $$ \limsup_{\substack{x\to x_0\\x<x_0}}\frac{g(x_0)-g(x)}{x_0-x}\leq \limsup_{\substack{x\to x_0\\x<x_0}}\frac{f(x_0)-f(x)}{x_0-x} $$ These are valid since $\liminf$ and $\limsup$ can be defined even if the limit doesn't exists or the term is unbounded. And now you can use that $f$ and $g$ are differentiable at $x_0$ which imply $$ h'(x_0)=\lim_{x\to x_0}\frac{h(x_0)-h(x)}{x_0-x}= \liminf_{\substack{x\to x_0\\x<x_0}}\frac{h(x_0)-h(x)}{x_0-x} $$ and $$ f'(x_0)=\lim_{x\to x_0}\frac{f(x_0)-f(x)}{x_0-x}= \limsup_{\substack{x\to x_0\\x<x_0}}\frac{f(x_0)-f(x)}{x_0-x} $$ So we get $$ h'(x_0)\leq \liminf_{\substack{x\to x_0\\x<x_0}}\frac{g(x_0)-g(x)}{x_0-x} \leq \limsup_{\substack{x\to x_0\\x<x_0}}\frac{g(x_0)-g(x)}{x_0-x}\leq f'(x_0) $$ Finally we use $f'(x_0)=h'(x_0)$ and conclude $$ h'(x_0)=\liminf_{\substack{x\to x_0\\x<x_0}}\frac{g(x_0)-g(x)}{x_0-x}= \limsup_{\substack{x\to x_0\\x<x_0}}\frac{g(x_0)-g(x)}{x_0-x}=f'(x_0) $$ Therefore $\lim_{\substack{x\to x_0\\x<x_0}} \frac{g(x_0)-g(x)}{x_0-x}$ exists and equals $f'(x_0)$ and $h'(x_0)$. Analogue we can prove that $\lim_{\substack{x\to x_0\\x>x_0}} \frac{g(x_0)-g(x)}{x_0-x}$ exists and equals $f'(x_0)$ and $h'(x_0)$. Together we get that $g$ is differentiable at $x_0$ and $g'(x_0)$ equals $f'(x_0)$ and $h'(x_0)$.

  • $\begingroup$ Thanks!! I think I get this now $\endgroup$ – Analysis is fun Nov 12 '17 at 10:05
  • 1
    $\begingroup$ Hopefully I fixed now all gaps in the proof. I rewrote some parts, because it was wrong. $\endgroup$ – Mundron Schmidt Nov 12 '17 at 10:27
  • $\begingroup$ You don't really need the limsup and liminf. Using the given conditions one can show that $f'(x_{0})=h'(x_{0})$ and then use Squeeze Theorem to get $g'(x_{0})=f'(x_{0})=h'(x_{0})$. $\endgroup$ – Paramanand Singh Nov 12 '17 at 14:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.